Analysis of spindle cooling system - Chan, Neol Christopher (2013)
Modern technology has shown that machine tool has played great roles in technology advances and is an ever-increasing productivity and competency throughout ages. The vital developments in industrialize machining was the usage of high speed machining which includes the motorized high speed spindle in manufacturing industries. This development has break the problems regarding delayed time and lower output in production line. However, heat was the primary enemy in this research.Overheating or excessive heat generation has caused lack in accuracy and precision in machining, exposure to wear and fatigue was the result of inefficient cooling system in the spindle cooling system. Thus, an analysis on the spindle cooling system through three parameters; different spindle operating speed, type of coolant and number of radiators has experimented. The result shows that higher operating speed produces more heat around the spindle. Moreover, results also demonstrate higher thermal stability in Ethylene glycol and water (EGW) compared to water at the peak of 6 hour respectively. In addition, EGW has a significant percentage of efficiency approximately 10% by using single and more than 15% using dual radiator at the minimal speed and astonishing efficiency of more than 39% and 52% for single and dual radiators respectively at speed, 18,000 rpm. In contrast, water only has below 10% of efficiency in any condition of experiment. In conclusion, EGW with single radiator is economically sufficient to remove heat generated in the spindle with efficiency of between 10% and 39% with lower power consumption of 6 Watts.